Impact of Perceived Skillset and Organizational Traits on Digital Wellbeing of Teachers: Mediating Role of Resilience - Yu, Fang; Mirza, Farhan; Chaudhary, Naveed Iqbal; Arshad, Rida; Wu, Yingyu (Frontiers in Psychology, 2022)
Given the current unstable and unpredictable circumstances, especially due to the COVID-19 education system has evolved, requiring frequently distinct skills, and coping behavior. This study intended to empirically test the impact of perceived skillset and organizational traits on teachers' digital wellbeing with the mediating role of three levels of resilience. To serve the cause, non-probability convenience sampling was chosen, and data was gathered through an online survey from 336 on-duty teachers in the education sector of Pakistan. The results of the study have been drawn by using the PLS-SEM partial least squares structural equation modeling technique through the Smart-PLS software 3.0 version. The findings show that perceived skillset had a positive and significant impact on digital wellbeing and organizational traits had an insignificant effect on digital wellbeing. Moreover, results indicate that organizational resilience and employee resilience positively mediate the relationship between perceived skillset and organizational traits on digital wellbeing. Similarly, findings illustrate that team resilience positively mediates the relationship between perceived skillset and digital wellbeing. Furthermore, results show that team resilience negatively and insignificantly mediates the relationship between organizational traits and digital wellbeing. Lastly, discussion, theoretical and practical implications were also discussed in this research article.